Image of the destination on interest in tourist visits ecotourism destination Clungup Mangrove Conservation - Ryan Gerry Patalo; Anisa Zuhria Sugeha; Yuliari Fernando Harlyson (Universitas Merdeka Malang, 2023)
This study aims to determine the influence of Instagram social mediaÂ and destination image on tourist visiting interest inÂ the Clungup Mangrove Conservation. The object of this research is Clungup Mangrove Conservation located in Tambakrejo Village, Sumbermanjing Wetan District, Malang Regency. Researchers conducted this study as an effort to provide answers that Instagram social media and destination images can affect the interest of tourists visiting the Clungup Mangrove Conservation. The study used quantitative methods by distributing questionnaires through Google Form. The results of this study showed that Instagram Social Media and Destination Image positively influenced Tourist Visiting Interest by 76.4%, while 23.6% was influenced by variables outside this study. Destination image has a significant influence than Instagram Social Media on Tourist Visiting Interest. Suggestions that can be given from the results of this study mean that the role of managers is needed in spreading the Clungup Mangrove Conservation. With the advancement of technology at this time, it will be very easy for managers to market destinations through social media such as Tik-Tok and Facebook so that destinations are increasingly known to tourists